Primary testicular non-Hodgkin’s lymphoma: a review article - Bhatia, Komal; Vaid, Ashok Kumar; Gupta, Sachin; Doval, Dinesh Chandra; Talwar, Vineet (São Paulo Medical Journal, 2007)
Primary testicular non-Hodgkin’s lymphoma was fi rst described as a clinical entity in 1866. It is a rare disease and accounts for 1% of all non-Hodgkin’s lymphoma, 2% of all extranodal lymphomas and 5% of all testicular neoplasms. It is the most common testicular tumor in males between sixty and eighty years of age. Testicular non-Hodgkin’s lymphoma is unique in its high incidence of bilateral involvement (8-38%), and it is also the most common bilateral testicular tumor. Testicular non-Hodgkin’s lymphoma has a predilection for spreading to non-contiguous extranodal sites, especially the central nervous system. Advanced-stage disease is usually managed with doxorubicin-based chemotherapy. For early-stage disease, opinion is divided regarding systemic chemotherapy following orchidectomy. The high incidence of spreading, especially to the central nervous system, leads to advocacy of the use of central nervous system prophylaxis with intrathecal chemotherapy. Prospective multicenter trials incorporating a large number of patients may lead to better guidelines for optimal management of this subtype of nonHodgkin’s lymphoma.